Catatonia with prominent psychosocial factors: A case report - Hiroto Noguchi; Yuki Omiya; Masahiro Hishiyama; Mariko Nakau; Sadayuki Hashioka (Psychiatry and Clinical Neurosciences Reports, 2026)
Abstract Background Catatonia is a psychomotor syndrome historically linked to schizophrenia but now recognized across diverse psychiatric, medical, and psychosocial contexts. Detailed reports of catatonia arising amid pronounced psychosocial vulnerability remain scarce. We describe catatonia in a patient with co‐occurring somatic symptom disorder, functional neurological symptom disorder (FNSD), and dissociative disorder that remitted with pharmacotherapy. Case Presentation A man in his 40's with chronic physical illness and recurrent fears of abandonment by his partner developed functional and dissociative symptoms after his partner's surgery was scheduled and was admitted following the sudden onset of fragmented, childlike speech. No specific neurological or medical cause was identified, and no schizophrenia or mood disorder was present. He developed stupor, mutism, posturing, negativism, mannerisms, and stereotypy, meeting DSM‐5‐TR criteria for catatonia; the Bush–Francis Catatonia Rating Scale (BFCRS) score was 22. Under lorazepam 3 mg/day and quetiapine 600 mg/day, the BFCRS improved to 3 by hospital Day 34, but worsened during dose reduction of either drug and improved on re‐escalation. He was discharged on hospital Day 98 with a BFCRS of 0, with no recurrence at 10 months. Conclusion Catatonia can arise in patients with co‐occurring somatic symptom disorder, FNSD, and dissociative disorder. In this patient, catatonia showed dose‐dependent re‐emergence during tapering of both lorazepam and quetiapine, with remission on re‐escalation. Even when psychosocial factors appear prominent, careful monitoring and gradual dose adjustment may be important for maintaining remission.